Neuroligin 3 Regulates Dendritic Outgrowth by Modulating Akt/mTOR Signaling - Xu, Jing; Du, Yong-lan; Xu, Jing-wei; Hu, Xiao-ge; Gu, Lin-fan; Li, Xiu-mao; Hu, Ping-hong; Liao, Tai-lin; Xia, Qiang-qiang; Sun, Qi; Shi, Lei; Luo, Jian-hong; et al. (Frontiers in Cellular Neuroscience, 2019)
Neuroligins (NLs) are a group of postsynaptic cell adhesion molecules function in synaptogenesis and synaptic transmission. Genetic defects in NL3, a member of the NL protein family, are associated with autism. Studies in rodents have found that mutations of NL3 gene lead to increased growth and complexity in dendrites in the central nervous system. However, the detailed mechanism is still unclear. In our study, we found that deficiency of NL3 led to morphological changes of the pyramidal neurons in layer II/III somatosensory cortex in mice, including enlarged somata, elongated dendritic length, and increased dendritic complexity. Knockdown of NL3 in cultured rat neurons upregulated Akt/mTOR signaling, resulting in both increased protein synthesis and dendritic growth. Treating neurons with either rapamycin to inhibit the mTOR or LY294002 to inhibit the PI3K/Akt activity rescued the morphological abnormalities resulting from either NL3 knockdown or knockout. In addition, we found that the hyperactivated Akt/mTOR signaling associated with NL3 defects was mediated by a reduction in PTEN expression, and that MAGI-2, a scaffold protein, interacted with both NL3 and PTEN and could be a linker between NL3 and Akt/mTOR signaling pathway. In conclusion, our results suggest that NL3 regulates neuronal morphology, especially dendritic outgrowth, by modulating the PTEN/Akt/mTOR signaling pathway, probably via MAGI-2. Thereby, this study provides a new link between NL3 and neuronal morphology.